tLyP-1–Conjugated Au-Nanorod@SiO2 Core–Shell Nanoparticles for Tumor-Targeted Drug Delivery and Photothermal Therapy - Xu, Baiyao; Ju, Yang; Cui, Yanbin; Song, Guanbin; Iwase, Yuichi; Hosoi, Atsushi; Morita, Yasuyuki (Langmuir, 2014)
Mesoporous silica-coated Au nanorod (AuNR@SiO2) is one of the most important appealing nanomaterials for cancer therapy. The multifunctions of chemotherapy, photothermal therapy, and imaging of AuNR@SiO2 make it very useful for cancer therapy. In this study, AuNR@SiO2 was functionalized to deliver hydrophobic antitumor drug and to heat the targeted tumor with the energy of near-infrared (NIR). To carry out the function of targeting the tumor, tLyP-1, a kind of tumor homing and penetrating peptide, was engrafted to AuNR@SiO2. The fabricated AuNR@SiO2–tLyP-1 which was loaded with camptothecin (CPT) showed a robust, selective targeting and penetrating efficiency to Hela and MCF-7 cells and induced the death of these cells. When the micromasses of these AuNR@SiO2–tLyP-1 internalized cells were irradiated by NIR illumination, all the cells were killed instantaneously owing to the increased temperature caused by the surface plasma resonance (SPR) of the internalized AuNR@SiO2–tLyP-1. Moreover, the systematic toxicity of CPT-loaded AuNR@SiO2–tLyP-1 on human mesenchymal stem cells (hMSCs) was minimized, because the AuNR@SiO2−tLyP-1 selectively targeted and penetrated into the tumor cells, and little hydrophobic CPT was released into the culture medium or blood. This study indicates that the AuNR@SiO2–tLyP-1 drug delivery system (DDS) has great potential application for the chemo–photothermal cancer therapy.